P58 Setting up an encephalitis multidisciplinary meeting in a tertiary neurology centre. Issue 3 (14th February 2019) - Bharucha, T; Brown, R; Bamford, A; Kaliakatsos, M; Hoskote, C; Breuer, J; Manji, H; Zandi, M
Abstract : Objectives: To improve the outcome of encephalitis in the region. Design: Service evaluation of the introduction of monthly encephalitis meetings attended by specialist neuroradiologists, neurologists and infection doctors. Subjects: Patient referred at the discretion of the clinician from local hospitals and the tertiary referral centre. Methods: Diagnosis confirmed at the MDT or as a direct result of the MDT discussion. Results: To be presented. Conclusions: Encephalitis is a rare and complex clinical syndrome that requires close communication between neurologists and infection doctors. Setting up an MDT established this interaction, and streamlines patient care. Further, it provides access to novel technologies such as metagenomic diagnostic approaches.